At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

The length of the longer leg of a right triangle is 14 ft longer than the length of the shorter leg [tex]\( x \)[/tex]. The hypotenuse is 6 ft longer than twice the length of the shorter leg. Find the dimensions of the triangle.

Select one:
A. Short leg [tex]\( = 11 \)[/tex], long leg [tex]\( = 25 \)[/tex], hypotenuse [tex]\( = 28 \)[/tex]
B. Short leg [tex]\( = 10 \)[/tex], long leg [tex]\( = 24 \)[/tex], hypotenuse [tex]\( = 26 \)[/tex]
C. Short leg [tex]\( = 9 \)[/tex], long leg [tex]\( = 23 \)[/tex], hypotenuse [tex]\( = 24 \)[/tex]
D. Short leg [tex]\( = 9 \)[/tex], long leg [tex]\( = 23 \)[/tex], hypotenuse [tex]\( = 28 \)[/tex]


Sagot :

To solve for the dimensions of the right triangle, we need to use the given relationships and the Pythagorean theorem. Let's break it down step by step.

1. Identify the Relationships:
- Let the length of the shorter leg be [tex]\( x \)[/tex] ft.
- The longer leg is 14 ft longer than the shorter leg, so the length of the longer leg will be [tex]\( x + 14 \)[/tex] ft.
- The hypotenuse is 6 ft longer than twice the length of the shorter leg, so the length of the hypotenuse will be [tex]\( 2x + 6 \)[/tex] ft.

2. Set Up the Pythagorean Theorem:
The Pythagorean theorem states that in a right triangle, the sum of the squares of the lengths of the two legs is equal to the square of the hypotenuse. Mathematically, this is:
[tex]\[ x^2 + (x + 14)^2 = (2x + 6)^2 \][/tex]

3. Expand and Simplify the Equation:
- First, expand both sides of the equation:
[tex]\[ x^2 + (x + 14)^2 = x^2 + 28x + 196 \][/tex]
[tex]\[ (2x + 6)^2 = 4x^2 + 24x + 36 \][/tex]
- So the equation becomes:
[tex]\[ x^2 + x^2 + 28x + 196 = 4x^2 + 24x + 36 \][/tex]

4. Combine Like Terms and Simplify:
- Combine like terms on both sides:
[tex]\[ 2x^2 + 28x + 196 = 4x^2 + 24x + 36 \][/tex]
- Move all terms to one side to set the equation to zero:
[tex]\[ 2x^2 + 28x + 196 - 4x^2 - 24x - 36 = 0 \][/tex]
[tex]\[ -2x^2 + 4x + 160 = 0 \][/tex]
- Multiply through by -1 to make it positive:
[tex]\[ 2x^2 - 4x - 160 = 0 \][/tex]

5. Solve the Quadratic Equation:
Using the quadratic formula [tex]\( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex]:
[tex]\[ a = 2, \quad b = -4, \quad c = -160 \][/tex]
[tex]\[ x = \frac{-(-4) \pm \sqrt{(-4)^2 - 4 \cdot 2 \cdot (-160)}}{2 \cdot 2} \][/tex]
[tex]\[ x = \frac{4 \pm \sqrt{16 + 1280}}{4} \][/tex]
[tex]\[ x = \frac{4 \pm \sqrt{1296}}{4} \][/tex]
[tex]\[ x = \frac{4 \pm 36}{4} \][/tex]
This gives us two solutions:
[tex]\[ x = \frac{4 + 36}{4} = 10 \quad \text{and} \quad x = \frac{4 - 36}{4} = -8 \][/tex]
Since a length cannot be negative, [tex]\( x = 10 \)[/tex] ft (shorter leg).

6. Calculate the Other Dimensions:
- Longer leg:
[tex]\[ x + 14 = 10 + 14 = 24 \text{ ft} \][/tex]
- Hypotenuse:
[tex]\[ 2x + 6 = 2(10) + 6 = 20 + 6 = 26 \text{ ft} \][/tex]

Therefore, the dimensions of the triangle are:
- Short leg = 10 ft
- Long leg = 24 ft
- Hypotenuse = 26 ft

The correct answer is b. Short leg = 10, long leg = 24, hypotenuse = 26.
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.